Is There an Exercise-Intensity Threshold Capable of Avoiding the Leaky Gut? - Ribeiro, Filipe M.; Petriz, Bernardo; Marques, Gabriel; Kamilla, Lima H.; Franco, Octavio L. (Frontiers in Nutrition, 2021)
Endurance-sport athletes have a high incidence of gastrointestinal disorders, compromising performance and impacting overall health status. An increase in several proinflammatory cytokines and proteins (LPS, I-FABP, IL-6, IL-1β, TNF-α, IFN-γ, C-reactive protein) has been observed ultramarathoners and triathlon athletes. One of the most common effects of this type of physical activity is the increase in intestinal permeability, known as leaky gut. The intestinal mucosa's degradation can be identified and analyzed by a series of molecular biomarkers, including the lactulose/rhamnose ratio, occludin and claudin (tight junctions), lipopolysaccharides, and I-FABP. Identifying the molecular mechanisms involved in the induction of leaky gut by physical exercise can assist in the determination of safe exercise thresholds for the preservation of the gastrointestinal tract. It was recently shown that 60 min of vigorous endurance training at 70% of the maximum work capacity led to characteristic responses of the leaky gut. It is believed that other factors may contribute to this effect such as altitude, environmental temperature, fluid restriction, age and trainability. On the other hand, moderate physical training and dietary interventions such as probiotics and prebiotics can improve intestinal health and gut microbiota composition. This review seeks to discuss the molecular mechanisms involved in the intestinal mucosa's adaptation and response to exercise and discuss the role of the intestinal microbiota in mitigating these effects.